Penyuluhan Stunting Pada Ibu Hamil Menyusui dan Wanita Yang Berpotensi Hamil di Negeri Saparua - Jusuf Leiwakabessy; Aprindo Steures Payara; Novanda Halirat; Meigy Nelce Mailoa (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Stunting often occurs in children aged 12-36 months. Children who experience stunting at this stage usually find it difficult to reach optimal height in the following period. Efforts to prevent stunting can be made if you know what stunting is. The aim of this activity is to increase community knowledge regarding stunting and its prevention. This activity is carried out by providing material from house to house using leaflets and education regarding the definition of stunting, causes of stunting in toddlers, ways to prevent stunting, and foods to prevent stunting. The target of this activity is pregnant and breastfeeding mothers and women who have the possibility of becoming pregnant. After this activity, it is hoped that the level of knowledge of the people of Saparua regarding stunting can increase in order to prevent the emergence of stunting again